Late-Quaternary paleoearthquakes along the Liulengshan Fault on the northern Shanxi Rift system - Sun, Wen; He, Honglin; Shi, Feng; Wei, Zhanyu; Sun, Haoyue; Su, Peng (Frontiers in Earth Science, 2023)
The Liulengshan Fault (LLSF), lies on the northeastern edge of the Ordos Plateau, is a controlling boundary fault in the northern part of the Shanxi Rift System (SRS). The displaced landforms show that the fault has undergone strong and frequent late-Quaternary seismic activities. In 1989 and 1991, two moderate-strong earthquake swarms (Ms=6.1, Ms=5.8) successively occurred in LLSF and GPS velocity shows that the area are extending at around 1-2 mm/a. However, there is no surface-rupturing earthquake reported on the LLSF in the historical record. Thus, the study of paleoseismic history and rupture behavior of paleoearthquakes in late-Quaternary on the LLSF is of fundamental importance for understanding the future seismic risk of this fault. To solve these problems, we conducted paleoseismological trench excavations at two sites on the LLNF to establish its paleoearthquake history. On the base of the field geological survey and interpretation of high-precision topographic data, we carried out large-scale fault mapping and excavated two trenches in Xujiabao and Luofengwa across the LLSF. Then, four events in Xujiabao trench and three events in Luofengwa trench are identified, respectively. Finally, combined with radiocarbon dating (C14), optical stimulated luminescence dating (OSL) and OxCal modeling, we constrained the ages of these events. Together with the previous results of paleoseismology in Yin et al. (1997), we consider that different segments of the LLSF may rupture together at the same time. Therefore, a total of 6 paleo-earthquake events since late-Quaternary have been finally confirmed at 44151-30881a BP, 40163-28045a BP, 28233-19215a BP, 16742-12915a BP, 12788-8252a BP and 8203-2300a BP, respectively. According to the empirical relationships between moment magnitude and rupture length, the best estimated magnitude is inferred to be in the range between Mw 6.9 and Mw 7.7. Considering the strong late-Quaternary activity and a long earthquake elapsed time, we propose that the LLSF might have a high seismic hazard potential in the near future.